Upaya Meningkatkan Hasil Belajar Matematika Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Example Non Example Pada Siswa Kelas XII SMAS Guppi Samata Gowa - Nur Aisyah; Azwan Anwar (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This research is classroom action research (PTK) carried out at SMAS GUPPI Samata, Gowa Regency which aims to improve mathematics learning outcomes by using the Example Non Example type cooperative learning model. The subjects of this research were class XII students with a total of 26 students. Data collection was carried out using learning outcomes tests. The collected data was analyzed using quantitative and qualitative analysis. The research results showed that the average score of student learning outcomes in cycle I reached an average of 82.38 and in cycle II reached an average of 86.15. The standard deviation in cycle I was 5.721 and in cycle II was 4.315. Based on the category of completeness of learning outcomes used, the score obtained for students' mathematics learning outcomes which were categorized as complete in cycle I was 73.07% and in cycle II it increased to 100%. From these results it can be concluded that there has been an increase in mathematics learning outcomes by using the Example Non Example type cooperative learning model.